Application of GARMA(1,1;1,d) model to GDP in Malaysia: An illustrative example. - Shitan, Mahendran; Pillai , Thulasyammal Ramiah (2011)
Gross Domestic Product (GDP) per capita is often used as an indicator of standard of living in an economy. GDP per capita observed over the years can be modelled using time series models. A new class of GARMA has been introduced in the time series literature to reveal some hidden features in time series data. In this paper, we illustrate the fitting of GARMA (1, 1; 1,) model to the GDP growth data of Malaysia which has been observed from 1955 to 2009. The estimation of the model was done using Hannan-Rissanen Algorithm.